Situating Gilgit-Baltistan in growing China Pakistan Interdependence: Post 9/11 Scenario - Zakir Hussain; Prof. Dr. Umbreen Javaid (Journal of Political Studies, 2018)
South Asia is the most pivotal region of the world which always endures with the geopolitical and geostrategic transformation of global politics and its repercussions. Due to the Post 9/11 geopolitical landscape, China-Pakistan has bound into undeniable rapport. Meanwhile the growing US-India strategic partnership enhanced the sense of insecurity in the region which compelled both nations become closer. Gilgit-Baltistan is the region which connects both states by land. This border region also has potential for conflict escalation between India and Pakistan because India claims Gilgit-Baltistan as her integral part and looks its strategic importance for shortest routes to Afghanistan and Central Asia. Anything happens in Gilgit-Baltistan regarding security concern will affect the Pakistan-China relationship. This paper is aimed at analyzing the significance of the geostrategic setting of GB in China and Pakistan relations.